Invertebrate abundance increases with vegetation productivity across natural and agricultural wader breeding habitats in Europe. (September 2022) - Silva-Monteiro, Miguel; Scheper, Jeroen; Pehlak, Hannes; Kurina, Olavi; Timonen, Sami; Pessa, Jorma; Pasanen, Esko; Verhoeven, Mo; Loonstra, Jelle; Piersma, Theunis; Robin, Frederic; Korniluk, Michał; et al.
Abstract: Grassland breeding waders have been steadily declining across Europe. Recent studies indicating a dramatic decline in grassland invertebrates' abundance and biomass, the key food of most grassland wader chicks, suggest a likely driver of the demise of waders. While agricultural intensification is generally inferred as the main cause for arthropod decline there is surprisingly little information on the relationship between land use intensity and total arthropod abundance in grasslands. Here, we explored those relationships across several key wader breeding habitats by surveying ground-active, aerial and soil-dwelling invertebrate communities in five European countries that range from natural undisturbed bogs to intensively managed grasslands. Using maximum vegetation growth and soil moisture content we investigated how they shape the size of the invertebrate community within and across different countries. We found predominantly positive relationships between grassland invertebrate abundance, biomass and body weight with increasing vegetation growth and soil moisture. Maximum vegetation growth was strongly positively related to ground-active invertebrate abundance and biomass and abundance of soil dwelling invertebrates (mainly earthworms). Body weight of aerial invertebrates furthermore increased with increasing maximum vegetation growth. Our results provide little support for the hypothesis that agricultural practices associated with intensification of grassland management result in an abundance decline of invertebrate prey for wader chicks. Conservation practices aiming to enhance wader chick survival require a careful balancing act between maintaining habitat productivity to secure high prey abundance, and keeping productivity low enough to maintain open swards that do not need to be cut before chicks have fledged.